Polyamines in conventional and organic vegetables exposed to exogenous ethylene - Rossetto, Maria Rosecler Miranda [UNESP]; Vianello, Fabio; Saeki, Margarida Juri [UNESP]; Lima, Giuseppina Pace Pereira [UNESP] (Elsevier B. V., 2015)
Relationships between endogenous levels of polyamines by thin layer chromatography (TLC) and gas chromatography (GC), nitrate and response to the application of ethylene were established between organic and conventional vegetables (broccoli, collard greens, carrots and beets), both raw and cooked. Responses to ethylene showed that organic plants were less responsive to the growth regulator. The levels of free polyamines obtained by TLC were higher in organic vegetables. Organic broccoli showed higher levels of putrescine (Put), and cooking resulted in lowering the overall content of these amines. Conventional collard green showed the highest level of putrescine in the leaves compared with organic. Tubers of carrots and beets contain the highest levels of Put. These plants also contain high levels of spermine. GC analysis showed the highest polyamines contents compared with those obtained by TLC. Cooking process decreased putrescine and cadaverine content, both in conventionally and organically grown vegetables. Organic beets contain lower NO3(-) compared with its conventional counterpart.
Keywords: Agmatine; Cadaverine; Cooking effect; Free polyamines; Nitrate content